Developing an engineering course in grains post-harvest operations - Ahmad, Mohammad Nur (Association for Engineering Education in Southeast Asia, 1987)
It has been widely recognised that grain post-harvest losses are high and commonly occurring in the South East Asian countries and particularly so in Malaysia. One of the many post harvest methods to overcome these losses is to train manpower that are involved in these activities. Graduate engineers in the field of agricultural engineering can provide the technical expertise in post-harvest operations. In this context a university education should provide a sound engineering course for its undergraduate students in this field. Such a course needs to emphasize design and operations aspects